2019
DOI: 10.1002/jcp.29279
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐omics analysis of tumor mutation burden combined with immune infiltrates in bladder urothelial carcinoma

Abstract: To explore the prognosis of tumor mutation burden (TMB) and underlying relationships with tumor-infiltrating immune cells in bladder cancer (BLCA).Transcriptome profiles and somatic mutation data from The Cancer Genome Atlas database by the GDC tool. A total of 437 samples were included, consisted of 412 BLCA patients and matched 25 normal samples. Specific mutation information was summarized and illustrated in waterfall plot. Higher TMB levels revealed improved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…Zhu et al found that the EP300 mutation was related to the TMB and promoted anti-tumor immunity in bladder cancer [27]. Zhang et al reported that immune genes such as CES1 and CSAG1 could be used as biomarkers for predicting the effects of immunotherapy through a multi-omics analysis [28]. Similarly, Pan et al discovered that Laylin is a prognostic marker of survival and is associated with immune in ltration in gastric and colon cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al found that the EP300 mutation was related to the TMB and promoted anti-tumor immunity in bladder cancer [27]. Zhang et al reported that immune genes such as CES1 and CSAG1 could be used as biomarkers for predicting the effects of immunotherapy through a multi-omics analysis [28]. Similarly, Pan et al discovered that Laylin is a prognostic marker of survival and is associated with immune in ltration in gastric and colon cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above conclusions, we speculated that TMB may play a crucial role in predicting the prognosis of endometrial cancer. Zhang et al (2019) performed a multi-omics analysis of TMB and immune in ltration in bladder urothelial carcinoma on the TCGA public platform, demonstrating that TMB may be an independent biomarker for survival prediction of bladder cancer (26). In this study, a similar methodology was utilized to analyze the relationship between TMB level and survival status in endometrial cancer.…”
Section: Discussionmentioning
confidence: 98%
“…With the continuous development of bioinformatics, we have the opportunity to obtain helpful resources about genomics and therapeutic responses from various public databases. Zhang C et al performed a multi-omics analysis of TMB and immune in ltration in bladder urothelial carcinoma using the Cancer Genome Atlas (TCGA) database (26). Given the impressive results achieved by immunotherapies, especially ICIs in the treatment of UCEC, we performed this study to explore the prognostic role of TMB and its potential association with immune in ltration in UCEC.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, ECM modi cation could not only promote tumor cells to escape, but also help generate and maintain the cancer stem cell niche [29]. Moreover, high in ltration of memory activated CD4 + T cell subsets were associated with prolonged OS and reduced risk of tumor recurrence in bladder cancer [30]. Chobrutskiy et al demonstrated that lower CDR3 region isoelectric point in T cell receptor was associated with better survival outcomes in bladder cancer [31].…”
Section: Discussionmentioning
confidence: 99%